Factors Effecting the Performance Efficiency of Official of Office of the Bangkok Metropolitan Administration Civil Service Commission - Saephu, Natcha; Noppanatwongsakorn, Rachen (Journal of Graduate MCU KhonKaen Campus, 2022)
This research of objective to: (1) to study the efficiency of government officials. Office of the Bangkok Civil Service Commission (2) to study the factors affecting the efficiency of government officials The Office of the Bangkok Civil Service Commission and (3) to suggest appropriate guidelines to increase efficiency for the performance of civil servants. Office of the Bangkok Civil Service Commission. This study is a quantitative research. The research population is A total of 178 civil servants from the Office of the Bangkok Civil Service Commission were tested for confidence. (Reliability) by taking the questionnaire that has been tested for accuracy, then checked and tested (Try Out) with people, non-sample population of 30 people to test the reliability of the questionnaire. by using the method to find the alpha coefficient (Alpha Coefficient) from 0.60 and up It can be said that the reliability is quite high. Show that the test is reliable can be applied to the sample group The tools used for data collection were questionnaires, statistics used for data analysis were descriptive statistics. The results of the research found that (1) the overall performance of government officials was at a high level. In order: strategy and strategy operational skills and management style, respectively. (2) Factors in the performance of government officials Office of the Bangkok Civil Service Commission of the respondents The results of the analysis of data on personal factors of the population group of 178 people found that most of them were females of 125 people representing 70.2% aged between 31-40 years of age 90 people representing 52.8% were educated at the level. Bachelor's degree: 97 people, equivalent to 54.5%, with a duration of work between 5-10 years, 58 people, accounting for 32.6%, and 85 people, representing 47.7% of the total number of bachelor's degrees. (3) Suggestions on knowledge workload The time spent working and the cost-effective use of resources.